P198 Is there a role for MRI cranial imaging in patients with non-small cell lung cancer being considered for radical treatment?. (2nd December 2011) - Laws, D; Adeniji, K; Ranaweera, N
Abstract : Introduction: Prior to undergoing radical treatment for Non-Small Cell Lung cancer (NSCLC) it is important to have accurate staging and exclude distal metastases to prevent patients undergoing futile inappropriate treatment. Guidelines1 have recommended consideration of MRI or CT imaging of the brain, especially in stage III disease. However, routine use in non-symptomatic patients has not been studied, particularly in conjunction with PET-CT scanning. In addition it is recognised that MRI is more likely to detect more and smaller lesions than CT brain. Our local policy is to offer MRI cranial imaging in all patients being considered for radical treatment in conjunction with PET scanning. We present a retrospective analysis of all these cases including follow-up and survival. Method: All patients discussed at lung cancer multi-disciplinary meeting (MDT) who were considered suitable for radical treatment were identified and offered PET-CT and MRI brain. Results of the scans, treatment received and disease free survival data were collected. Results: There was data available on 115 cases. Eight were found to have cerebral metastasis on MRI scanning. 6/8 (75%) had with lung lesions of more than 3 cm and or a nodal status more than N>1 on initial CT staging. All eight died within 6 months of diagnosis. 2/8 failed to meet criteria with one patient's intracranial lesions probably due to co-existing breast cancer and the other refusing biopsy and therefore may not have been NSCLC. Conclusion: Eight patients would have had radical treatment inappropriately if MRI brains had not been performed. Previous studies suggest <10% pick up of cerebral metastases in non-symptomatic patients pre-PET scanning era. Our series shows 7%. We therefore suggest a cut-off from stage 1B –11A in the 7th TNM classification as an indication to request a contrasted MRI brain as part of the staging protocol with NSCLC where radical therapy is being contemplated.